Understanding Cost Drivers of Identification Systems - World Bank (World Bank, Washington, DC, 2018)
Approximately one billion people globally lack government-recognized identification. As a consequence, they face barriers to accessing critical services and exercising their rights. Robust, inclusive, and responsible foundational identification (ID) systems2 can be transformative for a country’s development and for the welfare of its poorest and most vulnerable populations by enabling financial inclusion, the empowerment of women and girls, access to basic services, social safety nets, and political participation. Moreover, at a systemic level, leapfrogging traditional paper-based approaches in favor of digital identification systems can generate significant benefits across the public and private sectors by increasing efficiency and accountability (chiefly through the reduction of fraud, leakages, and waste in public programs) as well as driving innovation in service delivery (through the use of mobile or digital payments, for instance). As governments across the globe are implementing new, digital foundational identification systems or modernizing existing ID programs, there is an urgent need to develop accurate estimations of the associated costs. There are a handful of existing analyses that have attempted to estimate the overall cost of foundational ID systems: for instance, Gelb and Diofasi Metz (2018) estimate that it is likely to cost a low income country roughly 0.6 percent of GDP to build a foundational ID system, or about $4–11 investment per registrant for enrolment and credential issuance. The same study cites figures for a few countries suggesting recurrent costs of around 0.06–0.1 percent of gross domestic product (GDP). As the authors point out however, few data points exist and these figures may not apply to different types of systems or to all countries.